Education and early detection of coronary heart disease in the community - Santi Herlina; Mareta Dea Rosaline; Helen Marcellina; Navisa Salsabilla; Mahare Girisa (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2024)
Coronary heart disease (CHD), commonly called coronary artery disease, refers to pathological processes that affect the coronary arteries, usually caused by atherosclerosis. One of the factors that influence the occurrence of atherosclerosis is the influence of people's lifestyles, the level of awareness of early detection of coronary heart disease, and the wrong dietary arrangements that cause a high risk of coronary heart disease in the community. This community service aims to increase public knowledge about managing and preventing coronary heart disease. The method used is education using media and early detection through health checks that can affect the occurrence of coronary heart disease, such as blood pressure, blood sugar values, and cholesterol. Knowledge of the risks of PKJ and early detection is expected to increase public awareness. It can be concluded that the activities of providing public education and early detection with health checks produce output that there is an increase in knowledge. Education related to coronary heart disease and health checks is expected to help conduct routine monitoring by educating families about early signs and prevention of coronary heart disease